Konsep Fundamental Manajemen Kurikulum dalam Meningkatkan Kualitas Program Pendidikan - Sofiatus Sobriyah (Lembaga Pengembangan Kinerja Dosen, 2025)
Curriculum management is a systematic, cooperative, comprehensive and organized effort in achieving educational goals. As an important element in the management of educational institutions, curriculum management involves curriculum planning, development, implementation and evaluation. This process aims to improve the quality of teaching-learning interactions and support the achievement of the vision and mission of educational institutions while adhering to national policies. The relationship between curriculum and learning is very close, where the curriculum becomes a guideline that covers the entire learning experience of students, while learning is the implementation of the curriculum. In the context of the Education Unit Level Curriculum (KTSP), curriculum development is carried out with the principles of competency-centeredness, relevance to the needs of learners, responsiveness to scientific developments, and a balance between national interests and local needs. These principles are directed to ensure the meaningfulness of the content, productivity, democracy, efficiency, and harmony with moral, religious, and social values. With effective curriculum management, educational institutions can create an optimal learning process to achieve educational goals.